1994
DOI: 10.1093/clinchem/40.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total mercury in biological specimens by cold vapor atomic fluorescence spectrometry

Abstract: An ultrasensitive method for determining total mercury concentrations in biological specimens is a prerequisite for monitoring exposure to chronic low-dose levels of Hg vapor such as those from dental silver amalgam fillings. The clinical consequences of such doses are currently in question. We describe an adaptation of a two-stage gold amalgamation preconcentration step combined with cold vapor atomic fluorescence spectrometric detection for Hg. At Hg concentrations of 40 and 350 nmol/L, the within-day assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Mercury is released from silver amalgam as elemental mercury (Hg). The measurement of Hg in biological materials is most commonly achieved by AAS (36, 37). The presence of mercury in pulpal tissue has been demonstrated by AAS in human and dog teeth (16, 18) and autometallographically (AMG) in minipig, monkey and rat teeth (8, 19, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Mercury is released from silver amalgam as elemental mercury (Hg). The measurement of Hg in biological materials is most commonly achieved by AAS (36, 37). The presence of mercury in pulpal tissue has been demonstrated by AAS in human and dog teeth (16, 18) and autometallographically (AMG) in minipig, monkey and rat teeth (8, 19, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the samples were transferred into 10‐ml calibrated flasks and made up to the volume with a solution of 5% (v/v) HNO 3 in 0.5 g/l K 2 Cr 2 O 7 . The reduction with a solution of 0.05% KBH 4 in 0.2% (w/v) KOH and analysis of total mercury content using hydride generation were performed with an atomic fluorescence spectrometer AF‐610A (Beijing Reili Instrument Co., China) by the method as described previously . The linear range of the mercury standard calibration curve was 0.10–1.60 ng/ml with a coefficient (r) of >0.999.…”
Section: Methodsmentioning
confidence: 99%
“…comm.). Mercury analysis performed by cold vapour atomic fluorescence spectrometry (Winfield et al, 1994) on the G983 and R87 specimens is reported here (Fig. 6), but cultivation analysis was not performed.…”
Section: Specimen Collection and Storagementioning
confidence: 99%